O comprometimento organizacional, a qualidade t??cnica e o tempo na equipe como antecedentes da centralidade dos atletas nas redes de confian??a de equipes esportivas - Genoino, Ronan Kayano (2016)
This study aimed to verify which leads an actor to have greater centrality in the trust networks, that verifies the relationship between organizational commitment, technical ability, and time in the team (independent variables) with the centrality of the athletes in the trust networks of team sports (dependent variable). This research was based on the theory of social networks, one of the topics most discussed in the social sciences in the last decade, specifically the trust networks, a kind of informal network that is formed by interpersonal trust relationships between the members of an organization. The study was a qualitative research with an exploratory descriptive done with athletes of the Centro Ol??mpico de Treinamento e Pesquisa. Questionnaires were applied in 49 athletes from three different teams, to collect socio-metric data, to measure the trust network (used the UCINET software), organizational commitment, technical ability of players and time in the team. Moreover, semi-structured interviews were conducted among coaches of the three teams. The results indicated that the research question in this project was answered, since the field provided empirical evidence about a positive relationship between organizational commitment, time in the team, technical ability, and the centrality of athletes in trust networks. The main practical application is the parallel that can be done with the managerial field, in which more committed and qualified professionals, with more time in the organizations, can enjoy greater confidence within the corporate environment, resulting in better organizational performance.